Vocal Cord Dysfunction: Analysis of 27 Cases and Updated Review of Pathophysiology & Management - George, Shibu; Suresh, Sandeep (International Archives of Otorhinolaryngology, 2019)
Introduction Vocal cord dysfunction is characterized by unintentional paradoxical vocal cord movement resulting in abnormal inappropriate adduction, especially during inspiration; this predominantly manifests as unresponsive asthma or unexplained stridor. It is prudent to be well informed about the condition, since the primary presentation may mask other airway disorders.Objective This descriptive study was intended to analyze presentations of vocal cord dysfunction in a tertiary care referral hospital. The current understanding regarding the pathophysiology and management of the condition were also explored.Methods A total of 27 patients diagnosed with vocal cord dysfunction were analyzed based on demographic characteristics, presentations, associations and examination findings. The mechanism of causation, etiological factors implicated, diagnostic considerations and treatment options were evaluated by analysis of the current literature.Results There was a strong female predilection noted among the study population (n = 27), which had a mean age of 31. The most common presentations were stridor (44%) and refractory asthma (41%). Laryngopharyngeal reflux disease was the most common association in the majority (66%) of the patients, with a strong overlay of anxiety, demonstrable in 48% of the patients.Conclusion Being aware of the condition is key to avoid misdiagnosis in vocal cord dysfunction. Fiberoptic laryngoscopy is the diagnostic gold standard to demonstrate paradoxical vocal cord adduction during an attack. A multidisciplinary approach should be adapted for the management, which should be specific and tailored for individual patients.
Keywords: Vocal Cord Dysfunction; paradoxical vocal cord motion; laryngopharyngeal reflux; asthma